Prevalence and antimicrobial resistance profiles of Escherichia coli isolated from free-range pigs: E. coli from free-ranging pigs - Zhang, Hongna; Zhao, Xiaonan; Wang, Xuepeng; Chang, Weishan (The Journal of Infection in Developing Countries, 2017)
Introduction: Numerous studies about antimicrobial resistant Escherichia coli (E. coli) of animal origins have been conducted around the world, most of them focus on bacteria from animals raised in intensive breeding farms, but systematic studies on antimicrobial resistance in E. coli of free range animals are still lacking. Methodology: This study aimed to investigate the prevalence and antimicrobial resistance profiles of E. coli from free-range pigs in Laiwu mountainous areas, eastern China. Results: Among 123 fecal samples, 123 non-duplicate E. coli were obtained with an isolation rate of 100.0％ (123/123). These E. coli showed the highest resistance rate to tetracycline (77/123, 62.6％), but all were sensitive to amoxicillin/clavulanic acid. Thirty-eight E. coli (38/123, 30.9％) showed multidrug resistance (MDR). Among 123 E. coli isolates, only 39 carried antimicrobial resistant genes detected in this study. Of these 39 isolates, blaTEM-1, blaCTX-M-14, blaCTX-M-15, qnrB, qnrD, qnrS1, floR and cfr genes were detected in 13, 9, 4, 7, 10, 7, 20, and 7 isolates, respectively. blaTEM-1 and blaCTX-M-14 genes were concomitantly detected in 6 isolates, and blaTEM, qnrB, qnrS and qnrD genes were concomitantly detected in 7 isolates. Conclusions: Free-ranging pigs may be regarded as a potential reservoir for antibiotic resistant genes.